Clinical profile and risk factors of patients presenting with acute myocardial infarction at RIMS, Imphal - Medo M Kuotsu; Dhanaraj Singh Chongtham; Nyamnyei Konyak; Lourembam Gayatri; Bijoy M (Asian Journal of Medical Sciences, 2024)
Background: Cardiovascular diseases are the leading cause of mortality in India. Ischemic heart disease is a result of an inadequate supply of blood to a portion of the myocardium caused by atherosclerotic disease of an epicardial coronary artery. The increasing incidence of myocardial infarction (MI) and associated mortality is a concern. Aims and Objectives: The aims and objectives of the study were to evaluate the clinical profile and determine the association of risk factors in patients presenting with acute MI. The study highlights the trend of occurrence of acute MI so as appropriate measures can be taken to mitigate the incidence of coronary artery disease (CAD). Materials and Methods: A cross-sectional study was conducted among 100 patients with acute MI admitted to the intensive coronary care unit and medicine wards of a tertiary center in North-East India. The study was carried out for a period of 2 years from September 2019 to August 2021. Results: The mean age of the study population was 63.13±10.47 years, with an age range from 41 to 90 years. The study population had 75% males and 25% females. The most common presenting symptom was chest pain in 96% of patients. Hypertension in 75% of patients was the most common risk factor studied. About 97% of patients had at least one cardinal risk factor for MI. Inferior wall MI in 47% of patients was the most common site of MI. The highest mortality was seen in those who presented with Killip Class IV. Conclusions: Increasing age and male gender predisposed to MI. The association of risk factors such as hypertension, diabetes, obesity, and family history was higher in females. To bring about a reduction in the risk of CAD, emphasis should be laid on the adoption of a healthy lifestyle particularly for those at risk of CAD.